1984
DOI: 10.3382/ps.0632062
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Growth in Poultry

Abstract: The hormonal control of growth in poultry and other species is complex. The available evidence supports the concept that growth hormone and the thyroid hormones are the principal hormones responsible for the attainment of normal growth in the domestic fowl. Other hormones, including somatomedins, epidermal growth hormone, sex steroids, and vitamin D metabolites, are also involved in the control of growth. Considerable study will be required for the elucidation of the exact roles of the various hormones in avia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 48 publications
2
48
1
Order By: Relevance
“…The data also suggested that GH concentrations decreased earlier in females (about 4 weeks of age) than in males (about 7 weeks of age) as observed previously in Pekin ducks [20], chickens [23] and turkeys [1]. In birds [20] and mammals [12], higher variable levels of GH observed in young compared to older animals and in males compared to females were related with pulsatile GH secretion of higher frequency and amplitude. A similar mode of secretion is suggested in Muscovy ducks by the very large coefficient of variation observed in our data until 8 weeks of age.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The data also suggested that GH concentrations decreased earlier in females (about 4 weeks of age) than in males (about 7 weeks of age) as observed previously in Pekin ducks [20], chickens [23] and turkeys [1]. In birds [20] and mammals [12], higher variable levels of GH observed in young compared to older animals and in males compared to females were related with pulsatile GH secretion of higher frequency and amplitude. A similar mode of secretion is suggested in Muscovy ducks by the very large coefficient of variation observed in our data until 8 weeks of age.…”
Section: Discussionsupporting
confidence: 67%
“…mL -1 between 1 and 9 weeks of age. In Pekin ducks, Scanes et al [20] showed that the decrease of plasma GH levels occurred earlier in females. In Muscovy ducks, a trend for higher GH concentrations in males compared to females was observed across the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…Since both thyroid hormones depressed circulation GH levels (confirming the results of Harvey, 1983), while exogenous GH is a potent stimulator of liver 5'-monodeiodinase in chickens (Kfhn et al, 1985), the decrease found in peripheral T 4 conversion can be related to the decreased GH levels after thyroid hormone treatment. The lower GH levels in birds treated with thyroid hormones may be regulated by an increased negative feedback mechanism on the release of thyrotropin-releasing hormone (TRH), which is known to be a potent GH-secretagogue (Scanes et al, 1984). Also, the rather high GH levels in the MMI-fed broilers can be related to the diminished negative feedback of circulating thyroid hormones on TRH release in these birds.…”
Section: Introductionmentioning
confidence: 99%
“…At a given age, they are more mature than males [12,18] Buvanendran [5] in a meat-type chicken line and 0.69 at 40 weeks by Singh et al [32] in a layer-type chicken line. Using REML in layer-type chicken lines, Hagger [14] and Tixier-Boichard et al [35] [20], Marks [21,22]) and the hormonal regulation of growth [4,29,37] contribute to the existence of sexual dimorphism. The correlation between the ratio of male to female body weight and sexual dimorphism was very high in chickens (0.98) which suggested concomitant evolution of both traits.…”
Section: Genetic Parameters Of Growth Traits In Both Sexesmentioning
confidence: 99%